2020
DOI: 10.1039/c9ay02246e
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification (LAMP) – review and classification of methods for sequence-specific detection

Abstract: This comprehensive review provides a systematic classification and a comparative evaluation of current sequence-specific detection methods for LAMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
265
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(269 citation statements)
references
References 185 publications
(205 reference statements)
0
265
0
4
Order By: Relevance
“…Compared with RT-PCR, the RT-LAMP has the advantages of simple operation, short reaction time, no need for special instruments, and high sensitivity, which is particularly suitable for rapid onsite detection. 29,30 Yan et al, developed a RT-LAMP assay for the detection of SARS-CoV-2 in clinical samples and designed ve sets of primers that target the orf1ab gene and the spike gene for optimization of this assay. The detection of 130 clinical samples by RT-LAMP showed that the sensitivity and specicity of this method were 100%, and the detection time was 26.28 AE 4.48 min, demonstrating the RT-LAMP assay is a powerful tool for the detection of SARS-CoV-2.…”
Section: Nucleic Acid-based Detection Methodsmentioning
confidence: 99%
“…Compared with RT-PCR, the RT-LAMP has the advantages of simple operation, short reaction time, no need for special instruments, and high sensitivity, which is particularly suitable for rapid onsite detection. 29,30 Yan et al, developed a RT-LAMP assay for the detection of SARS-CoV-2 in clinical samples and designed ve sets of primers that target the orf1ab gene and the spike gene for optimization of this assay. The detection of 130 clinical samples by RT-LAMP showed that the sensitivity and specicity of this method were 100%, and the detection time was 26.28 AE 4.48 min, demonstrating the RT-LAMP assay is a powerful tool for the detection of SARS-CoV-2.…”
Section: Nucleic Acid-based Detection Methodsmentioning
confidence: 99%
“…For the RNA amplification, reverse transcription step must be done before the LAMP process, which is known as the RT-LAMP method. Detection of the amplicon is usually performed by observing the precipitates of magnesium pyrophosphate by-product, DNA-binding dyes, gel electrophoresis, or real-time fluorescence [30,90,91].…”
Section: Isothermal Amplification-based Methodsmentioning
confidence: 99%
“…Barcoding is already used for research but implementing the same for COVID-19 diagnostic purposes requires proper validation and scaling up. For easy digitalization of results and data management, computer integration of optical sensors for barcode scanning or use of nanomaterials that change electrical or magnetic properties upon binding to target sequences can prove beneficial [91][92][93]. Another report mentions analyzing the color change of gold nanoparticles in a salt solution on amplification of the viral genomic DNA [94].…”
Section: Challenges and Prospectsmentioning
confidence: 99%